1144. Modern Problem, Medieval Cure-Resistant Aeromonas in Medicinal Leeches. (26th November 2018) - Parkes, Leighanne Olivia; Barker, Kevin; Poutanen, Susan M; Grant, Jennifer M; Libman, Michael; Leis, Jerome; Stapleton, Patrick; Silverman, Michael; Hota, Susy
Abstract: Background: Medicinal leeches are used primarily in plastic and reconstructive surgery when venous congestion threatens tissue viability. The associated infection risk ranges from 4.1 to 20%. Prophylactic antimicrobials such as fluoroquinolones (FQ) or trimethoprim-sulfamethoxazole (SXT) are recommended and target commonly isolated pathogen and gut symbiont, Aeromonas . However, resistance to these agents has been reported and detected in leeches, including at hospital systems across Canada that acquire their stock from the same supplier. Our objective was to describe the local epidemiology of leech-related Aeromonas resistant to one or more commonly used prophylactic agents, and determine if such resistance originates from the common supplier. Methods: Six hospital systems across Canada using leech therapy, purchased from the same supplier, were surveyed. A 5-year retrospective review of all antimicrobial resistant leech-related Aeromonas, derived from clinical, leech, and tank fluid specimens was performed. All Aeromonas resistant to either FQ or SXT were included, and retained frozen isolates from each system were analysed by pulse-field gel electrophoresis (PFGE) using a published Aeromonas protocol. Results: All six hospital systems reported leech-related Aeromonas resistant to one or more antimicrobials, totalling 15 isolates. Three systems only reported data from the last year. Four systems used FQ and two used SXT as prophylaxis. Fifteen of 15 were either FQ resistant or intermediate, and four of 15 were SXT resistant. Three of 10 isolates tested for ceftriaxone (CRO) susceptibility were resistant. Five of 15 of the isolates were resistant to two or more agents. Of the two leech quality control isolates, 2/2 were FQ resistant and 1/2 was FQ, SXT and CRO resistant. Only three isolates, each from a different, geographically distinct hospital system, had been retained. PFGE analysis indicated 2/3 are closely related (Figure 1). Conclusion: Our preliminary investigation suggests that the presence of FQ and SXT resistance in leech-related Aeromonas might be more common than previously suspected, and that such resistance might originate from a common source. A broader study of the molecular epidemiology of leech-related Aeromonas is warranted. Disclosures: All authors: No reported disclosures.